Optimalisasi Kinerja Karyawan Melalui Penempatan Kerja Dan Pengembangan Karir - Ervina Widiastuti; Faizal Mulia Z; Nor Norisanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
PT Pratama Abadi Industri is a company that absorbs enough manpower, this company considers the placement of employees to be an important issue to pay attention to, among others, in the context of optimizing existing human capabilities in order to produce employees who excel according to the abilities and knowledge needed. The purpose of this study was to measure the effect of job placement and development on employee performance. The method used in this research is descriptive method and associative method with a quantitative approach. The sampling technique in this study used probability sampling using simple random sampling, which involved 100 employees at PT Pratama Abadi Industri. The data analysis technique used is multiple linear regression analysis, including the coefficient of determination test, multiple correlation coefficient, simultaneous test (F test) and partial test (T test). The results of the study, using the F test the probability value of sig. 0.00 < 0.05 which means that joint work placement (X1) and career development (X2) have a significant effect on employee performance (Y). While the t test shows that work placement (X1) hasn’t a significant effect on employee performance (Y) and career development (X2) has a significant effect on employee performance (Y). Keywords: Work Placement; Career development; Employee performance.